Mapping Antimicrobial Resistance in Staphylococcus epidermidis Isolates from Subclinical Mastitis in Danish Dairy Cows - Desiree Corvera Kløve; Mikael Lenz Strube; Peter M. H. Heegaard; Lærke Boye Astrup (Antibiotics)
Background/Objectives: Although Staphylococcus epidermidis is a key cause of subclinical mastitis in Danish dairy cows, its sensitivity to antimicrobials remains unexplored. Here, we analyzed sixty S. epidermidis isolates derived from 42 dairy cows across six conventional dairy herds in Denmark. Methods: Phenotypic resistance was measured by antimicrobial susceptibility testing and minimum inhibitory concentration (MIC) analysis, and genotypic resistance was examined through whole-genome sequencing and identification of antimicrobial resistance genes (ARGs). Correspondence between phenotypic and genotypic resistance was then evaluated by Cohen’s kappa statistics. Furthermore, the presence of plasmid replicon genes and the strain diversity among the S. epidermidis isolates was investigated to associate these findings with the observed AMR patterns. Results: Results showed that 30/60 isolates (50.0%) were resistant to penicillin phenotypically, while 35/60 (58.3%) were positive for a corresponding blaZ gene (κ = 0.83, p < 0.01). A fosB gene, encoding fosfomycin resistance, was detected in all 60/60 isolates (100.0%), but fosfomycin resistance was not analyzed phenotypically. Based on MIC analysis, 3/60 isolates (5.0%) were multi-drug resistant, showing resistance towards penicillin, erythromycin, and tetracycline. However, in 11/60 genomes (18.3%), ARGs encoding resistance towards ≥3 antimicrobial classes (e.g., beta-lactams, phosphonic acid, tetracyclines, aminoglycosides, macrolides, lincosamides, and fusidane) were detected. Eleven different ARGs were detected among the 60 isolates in total. No methicillin-resistant Staphylococcus epidermidis (MRSE) were recorded. Results further showed that each herd had one primary sequence type (ST) and resistance profile associated with it, and plasmid-mediated horizontal gene transfer of ARGs was indicated This study underscores the importance of routine resistance surveillance and species-specific diagnoses to improve treatment outcomes and ensure prudent use of antimicrobials.